Prevalence, Clinico-Demographic Profile, and Antimicrobial Susceptibility of MRSA Infections in a Tertiary Hospital in Western India: A Retrospective Study - Shilpi Gupta1; Ekadashi Rajni1*; Afreen Ali1; Anindita Kurmi1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) has a high prevalence in hospital settings in India and imposes a serious economic burden on healthcare resources. Understanding the local prevalence and evolving antimicrobial resistance patterns of MRSA is crucial for guiding effective treatment strategies. This study aims to determine the prevalence, clinico-demographic profile, and antibiotic susceptibility patterns of MRSA and methicillin-susceptible Staphylococcus aureus (MSSA) isolates. Methods: This retrospective study analyzed Staphylococcus aureus isolates collected between June 2021 and May 2023 from blood, pus, sterile body fluids, respiratory, and urine samples at the Microbiology laboratory of Mahatma Gandhi Hospital. Isolates were identified as S. aureus and tested for methicillin resistance using the Vitek 2 Compact system, which employs an advanced colorimetry method for identification and determines the minimum inhibitory concentration (MIC) using a broth microdilution method for antimicrobial susceptibility testing. Results: Of the 481 Staphylococcus aureus isolates analyzed, 264 (55%) were identified as MRSA. Among the MRSA isolates, the most common source was pus/wound infections (59%), followed by bloodstream infections (22%). MRSA isolates showed a susceptibility rate of 56% to gentamicin and 45% to clindamycin, but only 14% to ciprofloxacin. However, 55% of MSSA isolates were resistant to ciprofloxacin. All MRSA isolates were susceptible to daptomycin, teicoplanin, vancomycin, and linezolid. Conclusion: Our findings underscore the need for continuous MRSA surveillance and emphasize tailoring local antibiotic guidelines based on resistance patterns. Targeted antimicrobial stewardship programs and reinforced infection control protocols, especially for pus/wound infections, are crucial to curb the spread of resistant strains.